1997
DOI: 10.1021/ja9613926
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Enantiomers and Racemate Formation in Two-Dimensional Crystals at the Water Surface from Racemic α-Amino Acid Amphiphiles:  Design and Structure

Abstract: Studies are presented on the two-dimensional (2-D) crystalline packing arrangements of enantiomerically pure and racemic α-amino acid RHC(NH3 +)CO2 - monolayers on water and on glycine aqueous solutions, as determined by synchrotron grazing incidence X-ray diffraction. The amphiphiles have been designed such that their racemic mixtures form 2-D crystals which are either heterochiral (for R = C n H2 n +1−, n = 10, 12, 16) due to the tendency for herringbone chain arrangements via glide symmetry or homochiral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
100
2
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 104 publications
(128 citation statements)
references
References 36 publications
(45 reference statements)
25
100
2
1
Order By: Relevance
“…These very small crystals are generally unstable due to their high surface tension, and thus have a tendency to transform to larger particles by Oswald ripening. In recent years, quantum dots were prepared mainly in matrices and also as self-assembled structures, such as reverse micelles, [10] zeolites, [11] polymers, [12] self-assembled monolayers, [13] biopolymers, [14] layered metal phosphonates, [15] and Langmuir±Blodgett (LB) films. [16,17] In the preceding communication, [18] we reported that spreading of tetracosanedioic acid HOOC(CH 2 ) 22 COOH (C 24 diacid) on surfaces of aqueous solutions containing di- …”
Section: Methodsmentioning
confidence: 99%
“…These very small crystals are generally unstable due to their high surface tension, and thus have a tendency to transform to larger particles by Oswald ripening. In recent years, quantum dots were prepared mainly in matrices and also as self-assembled structures, such as reverse micelles, [10] zeolites, [11] polymers, [12] self-assembled monolayers, [13] biopolymers, [14] layered metal phosphonates, [15] and Langmuir±Blodgett (LB) films. [16,17] In the preceding communication, [18] we reported that spreading of tetracosanedioic acid HOOC(CH 2 ) 22 COOH (C 24 diacid) on surfaces of aqueous solutions containing di- …”
Section: Methodsmentioning
confidence: 99%
“…[23] Tailoring the chemical composition along the alkyl chain allows the patterning of organic monolayers on the nanometer scale, [24] and this has also been shown for systems at the liquid/air interface, where the molecules lie with their long axes parallel to the substrate. [25,26] Self-assembly has also been used to directly form a nanotemplate that does not require further manipulation by an SPM probe. Based on metal complexation, examples have been reported of the formation of welldefined coordination arrays on surfaces (metallo-grids), which were found to possess interesting electronic, magnetic, and structural properties.…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach has recently been applied for achieving spontaneous separation in two-dimensional crystals. 42 The most important symmetry elements by which organic molecules are related in three-dimensional crystals are, of course, translation, center of inversion, twofold screw axis, and glide plane. In the two-dimensional counterpart at a liquid surface for amphiphilic molecules that are specifically oriented vis-à-vis the water surface, the situation is simpler.…”
Section: Control Of Spontaneous Separation In Two-dimensional Crystalsmentioning
confidence: 99%
“…43 Recently a focus was put on the design of ␣-amino acid amphiphiles, that their racemates would spontaneously separate or form a racemic compound. 42 Thus monolayers of amphiphiles of the type C n H 2n+1 CH(NH 3 + )CO 2 − , labelled C n -gly, n = 10,12,16, have been studied by grazing incidence X-ray diffraction (GID) (Fig. 3).…”
Section: Control Of Spontaneous Separation In Two-dimensional Crystalsmentioning
confidence: 99%